Adaptation as audiovisual recreation: the fragmentary and grotesque petronius of Fellini - Bulhoes, Marcelo Magalhaes [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Arquitetura Artes & Comun, 2018)
The main purpose of this study is to analyze Federico Fellini's film adaptation of a classical work, the Satyricon of Petronius. In Fellini's Satyricon (1969), the adaptation was made in the prestigious context of the so-called auteur cinema, which placed value on the aesthetic idiosyncrasies of individual filmmakers. The key is to evaluate the process of audiovisual adaptation as an attitude of deliberate recreation, through the articulation between the fragmentary and the grotesque, fundamental aspects of Fellini's cinematography.
Keywords: Audiovisual Adaptation; Cinema; Fragmentary; Grotesque